The Effect of Synthesized Triazole and Ciprofloxacin Conjugated Peptide Compounds on Biological systems: Biological effects of Triazole and Ciprofloxacin Conjugated Peptide. - Behnoosh Safaei; Maryam Baharloui; Kiana Esfandiari Mazandaran; Golrokh Farnam; Arash Mahboubi; Mohammad Hassan Houshdar Tehrani; Farshad H. Shirazi (Iranian Journal of Pharmaceutical Sciences, 2022)
Breast cancer is the most common cancer among women and only second in terms of cancer-related death in women. Finding new approaches to treat such cancers is critically important anti-cancer peptides (ACPs) offer the possibility of efficient-cancer drugs, and therefore, the development of drug delivery systems using ACPs as a synergism factor is an attractive strategy to address the current drawbacks of cancer therapeutics. This work investigated the cytotoxicity for a series of synthesized compounds based on triazole or ciprofloxacin conjugated peptides against T-47D breast cancerous cells and possible antibacterial effects. Wang resin was used for constructing peptide sequences on a solid support using the method of solid-phase peptide synthesis (spps) with the Fmoc strategy. Cytotoxicity of the synthesized peptide compounds was evaluated by MTT assay. The antimicrobial effect of synthesized peptide compounds was evaluated by agar well diffusion and Broth microdilution method. Most of the peptide compounds showed a cytotoxic effect toward T-47D cells. The antimicrobial effect of the peptide compounds was examined by agar well diffusion test and broth microdilution method. E. coli and S. aureus strains have shown the least amount of resistance. In the end, we suggest a new design based on these compounds and modifications to gain better anti-cancer agents